MOOD REALIZATION IN EFL CLASSROOM INTERACTION: A FUNCTIONAL GRAMMAR APPROACH - Widiastuti, Rizki (2016)
This research investigates mood realization in a classroom interaction. The research focuses on the realization of mood system and the reason certain mood types chosen by the teacher in an EFL classroom interaction. Qualitative research with descriptive design was used in conducting this research. The data of this research is the utterances of the teacher and the students when they were conducting teaching-learning process in one of English courses in Bandung. The data are taken from classroom observations and audio-video recordings. The data were recorded, transcribed, and interpreted then analyzed using systemic functional grammar theory suggested by Halliday. From the analysis it was found that the teacher has more utterances (54%) than the students (46%). The findings imply that the teacher has domination in time and length of speaking. From twelve speech functions, the teacher applied only nine of them yet the students applied all speech functions. The teacher realized the speech functions in 90% typical mood types and 10% non-typical mood types, yet the students realized the speech functions in 99% typical mood types and 1% non-typical mood types. From the analysis, it can be concluded that by realizing speech functions in typical mood types, it is a way of the teacher to preserve the power, but in the same time, the teacher also realized non-typical mood types, which means that the teacher is trying to build solidarity and reduce the distance made by the status difference. Key words: Systemic Functional Grammar, interpersonal meaning, mood realization, speech function, mood types, classroom interaction.